Estimation and Evaluation of Brain Biogenic Amines for Anticonvulsant Activity Of Annona Squamosa Linn. Leaves in Mice - Porwal, Mayur; Sharma, K; Sharma, P.K. (Asian Journal of Pharmaceutical Research and Development, 2013)
The ethanol extract of the leaves of Annona squamosa Linn. showed marked protection against convulsions induced by chemo convulsive agents in mice. The catecholamines contained were significantly increased in the processed extract treated mice. The amount of GABA, which is most likely to be involved in seizure activity, was increased significantly in mice brain after six week treatment. Results of the present study revealed that the processed extract showed a significant anticonvulsive property by altering the level of catecholamine and brain amino acids in mice.